Draft genome sequence of Weissella soli strain DB-2, isolated from nukadoko - Fukuda, Daisuke; Nolasco Hipolito, Cirilo (American Society for Microbiology, 2022)
Weissella soli strain DB-2 is a lactic acid bacterium that was isolated from nukadoko in Japan. We report the draft genome sequence of Weissella soli strain DB-2 to determine the presence of the genes responsible for exopolysaccharide biosynthesis, with the aim of further probiotic evaluation.
Keywords: Weissella soli; Secuenciación genómica; Exopolisacáridos